(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article is devoted to the study various approaches of defining characteristics of inventories in industry. The main methods of forming estimates of reserves, and their initial fair value are focused upon. Existing methods of accounting for inventories enterprises are analyzed and critically evaluated. Existing methods of assessment of disposal of stocks, peculiarities of their reflection in accounting process, their advantages and disadvantages are studied. External and internal factors that influence the choice of estimation method of inventory are determined. Areas of modern studies in the evaluation of disposal of stocks discussed in the scientific literature are identified. Positive and negative implications of each specific evaluation method of disposal of inventories in enterprises are analyzed